2015
DOI: 10.1007/s00253-015-6897-2
|View full text |Cite
|
Sign up to set email alerts
|

Iron management and production of electricity by microorganisms

Abstract: The increasing dependency on fossil fuels has driven researchers to seek for alternative energy sources. Renewable energy sources such as sunlight, wind, or water are the most common. However, since the 1990s, other sources for energy production have been studied. The use of microorganisms such as bacteria or archaea to produce energy is currently in great progress. These present several advantages even when compared with other renewable energy sources. Besides the energy production, they are also involved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…The size of the FeCPs is highly reproducible (average diameter 5.6 nm; Figure A,C; Figure S4), similar to cytochromes, FeS proteins, or Fe-transporters (Table S3). , Compared to the cell surface, FeCP are enriched in Cu (Figure D) which is specific for Fe oxidases . The density of these particles on the bacterial surface is relatively high (they cover about 2% of cell surface), and they are more or less equally distributed over the cell (Figure A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The size of the FeCPs is highly reproducible (average diameter 5.6 nm; Figure A,C; Figure S4), similar to cytochromes, FeS proteins, or Fe-transporters (Table S3). , Compared to the cell surface, FeCP are enriched in Cu (Figure D) which is specific for Fe oxidases . The density of these particles on the bacterial surface is relatively high (they cover about 2% of cell surface), and they are more or less equally distributed over the cell (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…The large particles have an irregular shape and size, and their origin is not clear. Based on their shapes, they might be either associates of the small FeCP or the initial steps of the formation of big Fe aggregates detected before on G. sulfurreducens cell surfaces. , It was demonstrated that planktonic G. sulfurreducens cells are able to acquire Fe from the surrounding medium and use it for extracellular respiration. , This effect is temperature dependent . To test the role of temperature in the formation of FeCPs, we performed HAADF and EDXS analyses of the cells cultivated at 25 °C.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is an essential redox element (between Fe 2+ and Fe 3+ forms) fundamental for biological processes that functions as a versatile cofactor for numerous proteins in biological processes. It plays a fundamental role in biological processes such as DNA replication and repair among others, but also as an electron donor and acceptor in many microorganisms such as Archae and Bacteria (Folgosa et al, 2015). Although iron is one of the most abundant elements on earth, its bioavailability is not as extensive as it would be expected, since at neutral pH its solubility is 0.1 M and 10 −8 M, for Fe 2+ and Fe 3+ , respectively.…”
Section: Introductionmentioning
confidence: 99%